Clinical and immunological characteristic and dynamic of the secondary diseases stage of HIV infection in children, taking into account the route of infection - V. B. Denisenko; E. M. Simovanyan (LLC "Diagnostics and Vaccines", 2021)
The purpose is to characterize the clinical picture, immune status and the natural history of HIV infection in the stage of secondary diseases in vertical and parenteral infected children.Materials and methods. A clinical, laboratory, instrumental, immunological examination of 132 children in the stage of secondary diseases infected with HIV in a vertical way (90; I group) and parenteral way in infancy (42; II group) was carried. Results. The clinical picture of HIV infection in the stage of secondary diseases included various combinations of HIV-associated symptoms, opportunistic infections, tumors, which determines the symptomatology of a particular stage. The use of the Cox regression mathematical model of proportional intensities demonstrated a reduction in the duration of stage 4A (RR 5.8; 95% CI 1.4-10.5; P < 0.001), 4B (RR 3.4; 95% CI 1.8-4.3; P < 0.001) and 4V (RR 4.8; 95% CI 1.2-8.9; P < 0.001) in children of group I. Using the method of multiplying Kaplan-Meier estimates, the significant differences between the time curves from the beginning of the 4A stage (Р = 0.044), 4B (P < 0.001) and 4V (Р = 0.029) before the transition to the subsequent stage in children of groups I and II were established. The content of CD4 lymphocytes in the blood in patients of group I was higher as compared with group II at the time of debut of stages 4A (Me 37.5%, IQI 33-40% and Me 22%, IQI 18-24%; Р < 0.001), 4B (Me 25%, IQI 22-28% and Me 20%, IQI 18-22%; Р < 0.001) and 4V (Me 14%, IQI 12-18% and Me 11%, IQI 10-14%; Р = 0.047).Conclusion. HIV infection in the stage of secondary diseases in children infected with the vertical way is characterized by more rapid progression compared with parenteral infected in infancy patients, which is associated with the immaturity of the immune system.